2020
DOI: 10.1016/j.ipm.2019.102064
|View full text |Cite
|
Sign up to set email alerts
|

A two phase investment game for competitive opinion dynamics in social networks

Abstract: We propose a setting for two-phase opinion dynamics in social networks, where a node's final opinion in the first phase acts as its initial biased opinion in the second phase. In this setting, we study the problem of two camps aiming to maximize adoption of their respective opinions, by strategically investing on nodes in the two phases. A node's initial opinion in the second phase naturally plays a key role in determining the final opinion of that node, and hence also of other nodes in the network due to its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Another paper by Dhamal 29 focuses on the optimal way to split the budget across multiple phases to increase the information diffusion under the IC model. Dhamal et al 30 proposed a two‐phase node investment framework where the node's final opinion in the first phase act as an initial biased opinion for the second phase.…”
Section: Related Workmentioning
confidence: 99%
“…Another paper by Dhamal 29 focuses on the optimal way to split the budget across multiple phases to increase the information diffusion under the IC model. Dhamal et al 30 proposed a two‐phase node investment framework where the node's final opinion in the first phase act as an initial biased opinion for the second phase.…”
Section: Related Workmentioning
confidence: 99%
“…Competitive aggressiveness includes not only the quantity of the competitive actions, but also the diversity of competitive varieties (Gnyawali and Madhavan, 2001;Andrevski et al, 2016;Panda, 2019;Zhang and Guan, 2019). There are many varieties of competitive actions, such as new product promotion, price adjustment and a series of other firm's actions to maintain or improve their competitive position in the coopetition network (Ndofor et al, 2011;Miri-Lavassani, 2017;Kim et al, 2018;Dhamal et al, 2020). Existing studies have shown that complex competitive actions require competitors to spend a lot of time to understand and then develop counterattack strategies (Tong and Reuer, 2010).…”
Section: Competitive Aggressiveness and Firm Performancementioning
confidence: 99%
“…Thus, popularity on social networks has become a topic of interest for researchers who want to establish analyses and studies regarding these areas of interaction [1], [2], [3], [4], [5], [6], [7], [8].…”
Section: Introductionmentioning
confidence: 99%